FYVE1/FREE1 Interacts with the PYL4 ABA Receptor and Mediates Its Delivery to the Vacuolar Degradation Pathway. Issue 9 (5th August 2016) - Belda-Palazon, Borja; Rodriguez, Lesia; Fernandez, Maria A.; Castillo, Mari-Cruz; Anderson, Erin M.; Gao, Caiji; Gonzalez-Guzman, Miguel; Peirats-Llobet, Marta; Zhao, Qiong; De Winne, Nancy; Gevaert, Kris; De Jaeger, Geert; et al.
Abstract : This study describes the turnover of ABA receptors through the endosomal pathway and provides insights on FYVE1 function in the ESCRT pathway to regulate ABA signaling. Abstract: Recently, we described the ubiquitylation of PYL4 and PYR1 by the RING E3 ubiquitin ligase RSL1 at the plasma membrane of Arabidopsis thaliana . This suggested that ubiquitylated abscisic acid (ABA ) receptors might be targeted to the vacuolar degradation pathway because such ubiquitylation is usually an internalization signal for the endocytic route. Here, we show that FYVE1 (previously termed FREE1), a recently described component of the endosomal sorting complex required for transport (ESCRT) machinery, interacted with RSL1-receptor complexes and recruited PYL4 to endosomal compartments. Although the ESCRT pathway has been assumed to be reserved for integral membrane proteins, we show the involvement of this pathway in the degradation of ABA receptors, which can be associated with membranes but are not integral membrane proteins. Knockdown fyve1 alleles are hypersensitive to ABA, illustrating the biological relevance of the ESCRT pathway for the modulation of ABA signaling. In addition, fyve1 mutants are impaired in the targeting of ABA receptors for vacuolar degradation, leading to increased accumulation of PYL4 and an enhanced response to ABA . Pharmacological and genetic approaches revealed a dynamic turnover of ABA receptors from the plasma membrane to the endosomal/vacuolar degradation pathway, which was mediated by FYVE1 and was dependent on RSL1. This process involves clathrin-mediated endocytosis and trafficking of PYL4 through the ESCRT pathway, which helps to regulate the turnover of ABA receptors and attenuate ABA signaling.